Implementasi Kegiatan Dzikir Pagi Al-Ma’surat dalam Membentuk Karakter Islami Siswa di SMP PGII 2 Bandung - Nur Sabila Sa'diah; Mujahid, Mujahid Rasyid; Ayi Sobarna (UNISBA Press, 2024)
Abstract.This thesis research discusses the implementation of al-ma'surat morning dhikr which is always routinely carried out at SMP PGII 2 Bandung. The purpose of the al-ma'surat dhikr activity is so that students have Islamic character. The type of research used in this study is a type of field research using a qualitative descriptive approach where the author wants to describe and explain the facts in the field. The objectives of this study are to: (1) To describe the application of dhikr al-ma'surat activities in shaping the Islamic character of students at SMP PGII 2 Bandung. (2) To describe the supporting and inhibiting factors of al-ma'surat dhikr activities in shaping the Islamic character of students at SMP PGII 2 Bandung. (3) To describe the positive impact of dhikr al-ma'surat activities in shaping the Islamic character of students at SMP PGII 2 Bandung. The results of the study show that the implementation of dhikr al-ma'surat has 4 stages, namely: Preparation stage, implementation stage, closing stage, and evaluation. Then the supporting factors in the implementation of al-ma'surat morning dhikr are the existence of al-ma'surat dhikr books, facilities in the form of mosques and the existence of a GDS (Prayer Discipline Movement) Team to discipline students, as well as a religious team to guide the implementation of al-ma'surat dhikr. In addition to supporting factors, there are also inhibiting factors in its implementation, such as students lacking focus during the implementation of dhikr al-ma'surat. Abstrak. Penelitian skripsi ini membahas mengenai implementasi dzikir pagi al-ma’surat yang selalu rutin dilakukan di SMP PGII 2 Bandung. Tujuan kegiatan dzikir al-ma’surat agar peserta didik memiliki karakter Islami. Jenis penelitian yang digunakan dalam penelitian ini adalah jenis penelitian lapangan (field research) dengan menggunakan pendekatan deskriptif kualitatif yang mana penulis ingin menggambarkan dan menjelaskan fakta-fakta yang ada di lapangan. Tujuan penelitian ini adalah untuk: (1) Untuk mendiskripsikan penerapan kegiatan dzikir al-ma’surat dalam membentuk karakter Islami siswa di SMP PGII 2 Bandung. (2) Untuk mendiskripsikan faktor pendukung dan penghambat kegiatan dzikir Al-ma’surat dalam membentuk karakter Islami siswa di SMP PGII 2 Bandung. (3) Untuk mendiskripsikan dampak positif kegiatan dzikir al-ma’surat dalam membentuk karakter Islami siswa di SMP PGII 2 Bandung. Hasil dari penelitian menunjukkan bahwa implementasi dzikir al-ma’surat ada 4 yaitu: Tahap persiapan, tahap pelaksanaan, tahap penutup, dan evaluasi. Kemudian faktor pendukung dalam pelaksanaan dzikir pagi al-ma’surat yaitu adanya buku dzikir al-ma’surat, fasilitas berupa Masjid dan adanya Tim GDS ( Gerakan disiplin Shalat) untuk menertibkan siswa, serta tim keagamaan untuk memandu pelaksanaan dzikir al-ma’surat. Selain faktor pendukung,terdapat juga faktor penghambat dalam pelaksanaannya, diantaranya seperti siswa kurang fokus saat pelaksanaan dzikir al-ma’surat.